2021
DOI: 10.3390/ijms221910390
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the APOBEC3 Family Is Associated with a Poor Prognosis and Influences Treatment Response to Raf Inhibitors in Low Grade Glioma

Abstract: Apolipoprotein B mRNA-editing enzyme catalytic polypeptide-like 3 (APOBEC3) has been identified as a group of enzymes that catalyze cytosine deamination in single-stranded (ss) DNA to form uracil, causing somatic mutations in some cancers. We analyzed the APOBEC3 family in 33 TCGA cancer types and the results indicated that APOBEC3s are upregulated in multiple cancers and strongly correlate with prognosis, particularly in low grade glioma (LGG). Then we constructed a prognostic model based on family expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Therefore, APOBEC3C expression denotes enhanced immune activity in the PDAC TME and predicts immunotherapy responses of PDAC. A previous pancancer analysis also revealed that APOBEC and kataegis are associated with programmed death-ligand 1/2 [ 63 ], and the potential of APOBEC for guiding immunotherapy has been affirmed in other tumours [ 64 , 65 ]. In addition, ongoing clinical trials are investigating the practicality of APOBEC in guiding precise tumour therapy [ 66 ], such as NCT02576444 (olaparib, phase II) and NCT03989089 (pembrolizumab, phase II).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, APOBEC3C expression denotes enhanced immune activity in the PDAC TME and predicts immunotherapy responses of PDAC. A previous pancancer analysis also revealed that APOBEC and kataegis are associated with programmed death-ligand 1/2 [ 63 ], and the potential of APOBEC for guiding immunotherapy has been affirmed in other tumours [ 64 , 65 ]. In addition, ongoing clinical trials are investigating the practicality of APOBEC in guiding precise tumour therapy [ 66 ], such as NCT02576444 (olaparib, phase II) and NCT03989089 (pembrolizumab, phase II).…”
Section: Discussionmentioning
confidence: 99%
“…Although Apobec1 and C-to-U editing have been linked to several biological processes, their dysregulation has also been associated with multiple diseases, including cancer (Luo et al, 2021; Swanton et al, 2015). Under these circumstances, the mechanisms regulating the correct enzyme activity might be lost and substrate availability might differ.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to generating point mutations in regulatory regions, APOBEC3s may further dysregulate gene expression by promoting increased oncogene copy number (Table 3 ). For example, higher APOBEC3 expression has been associated with increased copy number variation of multiple Ras/MAPK regulatory genes such as ATP2B4 , MAPKAPK2 , and USP15 in glioma [ 51 ]. Amplification of EGFR and CDK4 —both known oncogenes—has also been observed in APOBEC3-high gliomas [ 51 ].…”
Section: Impact Of Apobec3s Through Mutagenic and Non-mutagenic Pathwaysmentioning
confidence: 99%
“…For example, higher APOBEC3 expression has been associated with increased copy number variation of multiple Ras/MAPK regulatory genes such as ATP2B4 , MAPKAPK2 , and USP15 in glioma [ 51 ]. Amplification of EGFR and CDK4 —both known oncogenes—has also been observed in APOBEC3-high gliomas [ 51 ]. The mechanisms through which APOBEC3s facilitate copy number changes remain unknown.…”
Section: Impact Of Apobec3s Through Mutagenic and Non-mutagenic Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation